2022
DOI: 10.1111/1440-1681.13676
|View full text |Cite
|
Sign up to set email alerts
|

Palovarotene inhibits the NF‐κB signalling pathway to prevent heterotopic ossification

Abstract: Heterotopic ossification (HO) is a common disease characterized by pain, dysfunction and calcification. The mechanisms underlying HO have not been completely elucidated. Palovarotene, a retinoic acid receptor γ agonist, significantly inhibits the formation of HO in vivo. However, its specific mechanism of action remains unclear. Therefore, we aimed to evaluate the signalling pathways related to the formation of HO as well as the mechanism of palovarotene action. We constructed in vitro and in vivo models of HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These findings suggest that different regulatory effects occur via different modulators that can affect NF-κB activity to exert different effects. In addition, in FOP, ACVR1 mutation-induced high TLR4 sensitivity can activate NF-κB signalling and interact with smad signalling in macrophages to promote inflammation in MSCs, and mTOR signalling may be involved in chondrogenic and osteogenic commitment to promote ectopic bone formation during FOP [ 16 , 100 , 102 , 126 , 128 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that different regulatory effects occur via different modulators that can affect NF-κB activity to exert different effects. In addition, in FOP, ACVR1 mutation-induced high TLR4 sensitivity can activate NF-κB signalling and interact with smad signalling in macrophages to promote inflammation in MSCs, and mTOR signalling may be involved in chondrogenic and osteogenic commitment to promote ectopic bone formation during FOP [ 16 , 100 , 102 , 126 , 128 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Smad signalling is important for the expression of osteogenic genes, including OCN, Sox9 and Runx2. Osteogenic gene expression can alter MSC fate by accelerating MSC differentiation into preosteoblasts for final ectopic bone formation [ 128 ]. Moreover, it has recently been demonstrated that during chondrogenesis triggered by activin A, mesenchymal stromal cells obtained from patients with FOP exhibit increased mTOR signalling [ 100 , 102 ].…”
Section: Nf-κb Signalling In Fopmentioning
confidence: 99%
See 1 more Smart Citation
“…Burn/tenotomy HO mouse models have also shown early increased levels of IL-6 and IL-1α in mice that form HO [ 187 ]. Recent studies have shown that the NF-κB signaling pathway plays an important role in tHO; when the NF-κB cascade was blocked, HO formation significantly decreased [ 188 ]. Similar to TGF-β pathways implicated in FOP, a recent study in a burn mouse model revealed that TGF-β1-producing macrophages are associated with HO, and a systemic reduction in macrophage-produced TGF-β levels helped to ameliorate HO [ 186 ].…”
Section: Inflammatory Control Of Homentioning
confidence: 99%
“…Palovarotene, a retinoic acid receptor gamma (RARγ) agonist, previously used in patients with emphysema [ 106 ], can inhibit the chondrogenesis phase in HO formation. Palovarotene influences BMP/SMAD-dependent pathway [ 107 ] and NF-κB signaling [ 108 ] preventing HO formation via endochondral ossification. In a trauma-induced HO rat model.…”
Section: Introductionmentioning
confidence: 99%